2014
DOI: 10.1186/1471-2393-14-130
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for performing a caesarean section in public hospitals in rural Bangladesh

Abstract: BackgroundIt is estimated that 18.5 million Caesarean Sections (CS) are conducted annually worldwide and about one-third of them are done without medical indications and described as “unnecessary”. Although developed countries account for most of the rise in the trend of unnecessary CS, more studies report a similar trend in developing countries, putting a strain on existing but limited healthcare resources, jeopardizing families' financial security and presenting a barrier to equitable universal coverage. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
62
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 18 publications
6
62
1
3
Order By: Relevance
“…[31,32]. Consistent with another study [33], the most common reasons for emergency CS in the current study were prolonged fetal distress, obstructed labor, and abnormal presentations such as breech or transverse presentations. The most frequent reason cited for planned CS was scarred uterus, which mostly reflects previous CS.…”
Section: Discussionsupporting
confidence: 90%
“…[31,32]. Consistent with another study [33], the most common reasons for emergency CS in the current study were prolonged fetal distress, obstructed labor, and abnormal presentations such as breech or transverse presentations. The most frequent reason cited for planned CS was scarred uterus, which mostly reflects previous CS.…”
Section: Discussionsupporting
confidence: 90%
“…33 They studied 100 physician mothers and revealed that 60% underwent caesarean section and 40% have normal vaginal deliveries between 2000 to 2015, 33%had caesarean section and 67% normal vaginal deliveries according to collected data before 2000.Radha et al explained that the rapid socioeconomic changes and the outlook towards medical intervention by the women, families and society are increasingly responsible for the current high incidence of caesarean section in many states and urban centers. 33 Findings of this study are not consistent with findings of Aminu et al 30 They found that the rate of caesarean sections was 21.2% which was conducted in the five public hospitals of Thakurgaon district of Bangladesh among 2503 deliveries during July to December 2011. Thakurgaon is a peripheral district situated northern part of Bangladesh.…”
Section: Discussioncontrasting
confidence: 57%
“…These findings are not in agreement with the findings of others. 30,32 Aminu et al observed that 68% of CS was performed as emergency. 25 Kaur, Singh and Kaur found higher number of emergency (52.3%) over elective (47.7%) caesarean sections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations